2011
DOI: 10.1089/ten.tea.2010.0398
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine-Controlled Formation and Function of Tissue-Like Aggregates by Primary Hepatocytes in Micropatterned Hydrogel Arrays

Abstract: The liver carries out a variety of essential functions regulated in part by autocrine signaling, including hepatocyteproduced growth factors and extracellular matrix (ECM). The local concentrations of autocrine factors are governed by a balance between receptor-mediated binding at the cell surface and diffusion into the local matrix and are thus expected to be influenced by the dimensionality of the cell culture environment. To investigate the role of growth factor and ECM-modulated autocrine signaling in main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 74 publications
(91 reference statements)
0
28
0
Order By: Relevance
“…[47] It has been suggested that enhanced cell-cell contact and the accumulation of autocrine factors, such as epidermal growth factor receptor (EGFR) ligands and deposited ECM, may be at play in enhancing hepatic phenotype in spheroid cultures. [6] Encapsulating spheroids in engineered 3D hydrogels has also been shown to enhance formation of organotypic structures in vitro ,[810] and can improve hepatocyte survival upon transplantation. [11]…”
Section: Introductionmentioning
confidence: 99%
“…[47] It has been suggested that enhanced cell-cell contact and the accumulation of autocrine factors, such as epidermal growth factor receptor (EGFR) ligands and deposited ECM, may be at play in enhancing hepatic phenotype in spheroid cultures. [6] Encapsulating spheroids in engineered 3D hydrogels has also been shown to enhance formation of organotypic structures in vitro ,[810] and can improve hepatocyte survival upon transplantation. [11]…”
Section: Introductionmentioning
confidence: 99%
“…Spheroids harvested from hanging drop arrays on Day 7 were stained with Alexafluor-488 conjugated phalloidin (green) and counter stained with nuclear stain, DAPI (blue). Cortical actin staining using phalloidin is commonly used to demonstrate cell–cell interactions and cell aggregates in 3D culture systems, including spheroids [1923]. Conjugated phalloidin stained the actin cytoskeletons of cells within spheroids.…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional presence and cell–cell interaction was further confirmed using confocal microscopy upon cytoskeletal actin and nuclei staining. Cortical actin staining using phalloidin is commonly used to demonstrate cell aggregates in 3D culture systems, including spheroids [1923]. The observance of cortical actin staining, as opposed to diffuse cytoplasmic staining and stress fiber staining of cells grown on monolayers, indicated the three-dimensional morphology of cells grown in attachment-free culture.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the dramatic improvement in function of primary rat hepatocyte co-cultures with fibroblasts on collagen-modified polydimethylsiloxane (PDMS, silicon rubber) substrates as a means to enhance oxygenation [62] may also arise in part due to more physiological presentation of the adhesion matrix or to partitioning of lipid-soluble hormones and nutrients into PDMS [63,64] providing a local depot regulating gene expression in a favorable manner. Similarly, culture in recessed wells may allow enhanced accumulation of autocrine factors that favorably regulate cell function [65]. …”
Section: Bioreactorsmentioning
confidence: 99%